Analysis of the Implementation of Annual Tax Reporting Policy among Personal Tax Payer in Indonesia - Dwikora Harjo; Fauzilah Salleh (Ilomata International Journal of Tax and Accounting, 2022)
Individual taxpayers awareness and compliance are predicted to be below expectations in numerous Indonesian regions, as evidenced by the yearly tax reporting (SPT), which is still below the expected aim. The number of taxpayers who submit the SPT is one indicator of compliance; the higher the number of taxpayers who report the SPT, the higher the level of compliance. The goal of this study is to look into how the Cileungsi Pratama Tax Service Office in West Java, Indonesia, implements annual tax reporting for personal taxpayers. The authors apply Van Meter Van Horn's Policy Implementation Theory to six test variables: standards and policy objectives, resources, inter-organizational linkages, implementing agent characteristics, social, economic, and political situations, and implementer disposition. The qualitative descriptive approach was adopted in this study. Observation, documentation, and interviews were utilised to collect data, which was then analysed through data reduction, data display, and drawing conclusions. The study's findings demonstrate that, from 2018 to 2020, individual taxpayers' yearly tax reporting at the Cileungsi Tax Office complied with applicable rules and regulations, but that it fell short of the aim.